Level of awareness on chemotherapy among cancer patients in Hospital Sultanah Nur Zahirah - Mohammad Sabri, Syuhadah Hanim; Abdul Ghafor, Fatin Syakirah; Zamri, Nur Sakinah (2013)
For this study, we are focusing on evaluating the level of awareness among cancer patients in Hospital Sultanah Nur Zahirah towards chemotherapy as well as to evaluate the effect of cancer treatment on their health status. Cancer patients' health status was measured using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). A questionnaire set to measure the awareness level was also used. Socio-demographic and clinical variables included were age, education, marital status, disease stage and types of treatment received since diagnosis. Forty cancer patients participated in the study. Results show that 34 (85%) of them had an average quality of life despite knowing the fact that they are diagnosed with cancer and the effect of cancer treatment. However, when being asked about chemotherapy and its details, most of them were not aware of it. Thirty (75%) patients out of 40 did not know the name of their own drugs. In conclusion, there are still many cancer patients that have low awareness towards chemotherapy.